Experimental and theoretical study on a heat pump driven open-air humidification dehumidification desalination system. (15th September 2020) - Lawal, Dahiru U.; Jawad, Saad A.; Antar, Mohamed A.
Abstract: This article presents experimental and theoretical investigations of a new configuration of an open-air open-water (OAOW), water-heated (WH), humidification-dehumidification (HDH) desalination system coupled with a vapor compression heat pump (HP) that considers two possibilities of energy recovery. Three different HDH system configurations including the basic system HDH-HP (without brine energy recovery), system A (basic system with brine energy recovery for pre-heating saline water), and system B (basic system with brine energy recovery for pre-heating ambient air) are presented. The performance of the basic system is examined experimentally; while that of systems A and B are assessed theoretically. Furthermore, the theoretical analysis is extended to the basis system to address the boundaries, constraints and limitations of experimental equipment, by analyzing the system performance at extended operation conditions. Results reveal that the developed model shows a good agreement against the experimental findings. Results also show that systems A and B portrayed superior performance over the basic system (especially system A), due to the energy recovery from the rejected brine. A maximum GOR of 2.72, RR of 2.56%, water productivity of 9.23 kg/h and a minimum freshwater cost of 15.14$/m 3 are attained experimentally, while theoretical results for system A revealed a maximum GOR of 5.06, RR of 3.98%, water productivity of 11.46 kg/h, and a minimum price of freshwater of 12.38$/m 3 . Graphical abstract: Heat pump operated HDH desalination system has been experimentally and theoretically investigated. A brine heat exchanger has been introduce to the system for the recovery of discharged brine thermal energy to heat either saline water or ambient air. The recovery of rejected brine thermal energy enhances the thermal and economic performances of the system. Image 1 Highlights: Experimental and analytical investigation of an open-air open-water, water heated HDH Desalination system. Energy recovery is considered both in the dehumidifier and in the rejected brine stream. Experimental system without heat recovery is capable of producing up to 221.5 L of distillate water per day. Energy recovery option A increases productivity to 275 L/day of fresh water. The system Gained output ration ranges between 2.72 and 5.